RYTUAŁ CZY CEREMONIA? ROZWAŻANIA NAD PRAKTYKAMI ŚLUBNYMI W KONTEKŚCIE PRZEMIAN W SFERZE ŻYCIA RODZINNO-MAŁŻEŃSKIEGO - Pińska, Aleksandra Magdalena (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
This article is concerned about the problem of the wedding practises which has not been undertaken by sociologists yet. The Author of the article explains the changes of wedding practises which appeared when the traditional society converted into the modern and next the postmodern society. The transformation of a wedding as a ritual passage into a ceremony is presented in this article from the point of the chosen aspects of the changes in family and marriage life. These aspects are: the fall in the number of marriages, the changes in the age of newlyweds, the lower age of sexual initiation and the higher number of cohabitation relationships.